The Impact of Glass Ceiling Factors on Job Performance of Women Employee - A field study on the employees of Damascus University in 2021 - - Boubes, Nour Mohamad; Kabalan, Samar Marouf (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aims to study the impact of Glass Ceiling factors (the family, cultural, individual, organizational and legal and legislative factors) on Job Performance of women employee. The method used is the analytical descriptive method since it is appropriate for this type of the study and it applied to a random sample stratified. To implement the aim of the study, the researchers designed questionnaire. The sample of the study consists of (348) of them were valid for statistical analysis. Then the results of the study were analyzed according to the Statistical Package for the Social Sciences (SPSS) program. The most important results of the study are: There is significant impact of the of the Glass Ceiling on Job Performance of women employee, and the change percentage in the dependent variable was.(72.3%) There is also significant impact of the family factors, cultural factors, individual factors, organizational factors and legal and legislative factors on Job Performance of women employee, and the organizational factors have the most influence and its change percentage in the dependent variable was (56%). There is no material difference in the answers to the Glass Ceiling and job performance questionnaire, attributed to personal and job variable (gender, social status, education level, age, years of the experience, job title, job position). The study made several recommendations, the most important of which are: holding seminars and intellectual conferences focusing the importance of women’s work and holding up training programs for developing and enhancing the administrative abilities and leadership skills for women, in addition to setting regulations, laws and legislation that encourage increasing women’s share of supervisory jobs.